Zinc alleviates stroke development through autophagy-mediated modulation of immune microenvironment - Qiu, Zijie; Liu, Xin; Li, Jie; Yin, Hongming; Luo, Jiankun; Lin, Zigang; Rexiati, Mayire; Abulaiti, Adila; Yasen, Aikebaier; Xing, Lifei; Aili, Dilihumaer; Meng, Bing; et al. (Frontiers in Immunology, 2025)
BackgroundStroke is a leading cause of death and long-term disability worldwide and is increasingly recognized as a neuroinflammatory, immune-mediated disease. Acute ischemia triggers robust activation and infiltration of innate immune cells, exacerbating neuronal injury. Zinc is an essential micronutrient with known immunomodulatory and autophagy-regulating roles, but its impact on stroke-driven neuroinflammation remains unclear. We aimed to investigate whether zinc protects against ischemic brain injury by modulating autophagy and the immune microenvironment.MethodsGenome-wide association (GWAS) and NHANES cohort analyses were performed to assess the association between zinc intake levels and stroke risk. Pathway enrichment analysis, PPI network construction, and diagnostic modeling were undertaken to identify ZIARs (zinc-responsive immuno-autophagic regulators). Immune infiltration analysis was used to assess immune cell infiltration levels in stroke. Cell-based ischemia-reperfusion experiments were conducted to evaluate zinc’s effects on autophagy and neuronal cell injury.ResultsHigher zinc levels were associated with lower stroke prevalence, as supported by GWAS results (OR ~0.141) and NHANES findings (adjusted OR ~0.96). Zinc-associated genes were predominantly enriched in autophagy and inflammatory signaling pathways, including PI3K-Akt and NF-κB. The diagnostic model identified ZIARs whose expression was closely linked to immune cell composition, particularly neutrophil infiltration, in stroke. In vitro experiment, zinc pretreatment of hypoxia-stressed neurons reduced cell death and oxidative damage, whereas autophagy inhibition abolished zinc’s neuroprotective effect. qPCR and Western blot analyses further confirmed that zinc attenuates RELA-driven autophagy overactivation, thereby promoting neuronal survival.ConclusionZinc confers neuroprotection in ischemic stroke by restoring autophagic flux and suppressing excessive innate inflammation through regulation of ZIARs. These findings underscore zinc’s neuroprotective role via immune-autophagy crosstalk and position it as a potential strategy for stroke prevention and intervention.